Intravenous contrast medium aggravates the impairment of pancreatic microcirculation in necrotizing pancreatitis in the rat - Schmidt, Jan; Hotz, Hubert; Foitzik, Thomas; Ryschich, Eduard; Buhr, Heinz J.; Warshaw, Andrew L.; Herfarth, Christian; Klar, Ernst (Annals of surgery, 1995)
Background - Previous reports demonstrated that radiographic contrast medium, as used in contrast-enhanced computed tomography, increases acinar necrosis and mortality in experimental pancreatitis. The authors studed the possibility that these changes may be related to an additional impairment of pancreatic microcirulation. - Methods - Fifty Wistar rats had acute pancreatitis induced by intraductal glycodeoxycholic acid (10 mmol/L for 10 min) and intravenous cerulein (5 μg/kg/hr for 6 hrs). After rehydration (16 mL/kg), pancreatic capillary perfusion was quantified by means of intravital microscopy at baseline before intravenous infusion of contrast medium (n = 25) or saline (n = 25), and 30 and 60 minutes thereafter. In addition to total capillary flow, capillaries were categorized as high-or low-flow (> or <1.6nL/min). - Results - Pancreatic capillary flow did not change in either high- or low-flow capillaries after saline infusion. However, contrast medium infusion induced a significant decrease of total capillary flow (p < 0.001). Analysis according to the relative flow rate revealed that this was primarity because of a significant additional reduction of perfusion in low-flow capillaries (p < 0.0001). Furthermore, complete capillary stasis was observed in 15.9 ± 3.4% after contrast medium as compared with 3.2 ± 1.2% after saline infusion (p < 0.006). - Conclusion - Radiographic contrast medium aggravates the impairment of pancreatic microcirculation in experimental necrotizing pancreatitis.
Gesehen am 04.09.2025